2009
DOI: 10.1007/s10310-009-0149-1
|View full text |Cite
|
Sign up to set email alerts
|

Allometric equations for accurate estimation of above-ground biomass in logged-over tropical rainforests in Sarawak, Malaysia

Abstract: Although allometric equations can be used to accurately estimate biomass and/or carbon stock in forest ecosystems, few have been developed for logged-over tropical rainforests in Southeast Asia. We developed allometric relationships between tree size variables (stem diameter at breast height (dbh) and tree height) and leaf, branch, stem and total above-ground biomass in two logged-over tropical rainforests with different soil conditions in Sarawak, Malaysia. The study sites were originally classified as mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 28 publications
3
69
1
1
Order By: Relevance
“…Applying the allometric equations to other study areas will cause uncertainties of forest ecosystem AGB estimates [11,[93][94][95]. In this study, several allometric equations were used to estimate the values of AGB of trees by species; however, the uncertainty from the used allometric equations was unknown.…”
Section: Uncertainty Analysis Of Forest Biomassmentioning
confidence: 99%
“…Applying the allometric equations to other study areas will cause uncertainties of forest ecosystem AGB estimates [11,[93][94][95]. In this study, several allometric equations were used to estimate the values of AGB of trees by species; however, the uncertainty from the used allometric equations was unknown.…”
Section: Uncertainty Analysis Of Forest Biomassmentioning
confidence: 99%
“…It is clear that both equations provided reasonable predictions of above ground biomass carbon across a range of groups of species and tree size classes. Various other researchers have compared allometric equations they developed for estimating above-ground biomass in tropical forest [30,31] with the pan-tropical equations developed by Chave et al [9], and concluded that general allometric equations were biased when applied at their sites. This was surprising to us, considering the results of the comparisons we made.…”
Section: Discussionmentioning
confidence: 99%
“…Basuki et al (2009) described that the establishment of allometric equations is related to the biophysical properties of trees, namely diameter at breast height (DBH), wood density and height. Several researchers formulated equations for the determination of biomass (Kato et al, 1978;Chambers et al, 2001;Chave et al, 2005;Kenzo et al, 2009;Blujdea et al, 2012,). Researchers such as Hamdan et al (2011);Hamdan et al (2014); Morel et al (2011);Saner et al (2012); Sato et al (2013) applied the established equations to calculate the forest biomass.…”
Section: Allometric Regression Model Equationsmentioning
confidence: 99%